A sentencing alternative for sex offenders - A study of decision making and recidivism - Milloy, Cheryl Darling; Schram, Donna; Miller, Lisa L. (Journal of interpersonal violence, 1995)
Society has been uncertain about how best to respond to sex offenders. One policy option is a community supervision and treatment alternative such as the Special Sex Offender Sentencing Alternative (SSOSA) enacted in Washington State in 1984. This study examines variables associated with the sentencing decision and compares recidivism rates of offenders granted the alternative and those who received the standard punishment (N = 646 convicted adult sex offenders). It also reports the results of a survey of key professionals regarding the sentencing alternative. Recidivism rates of the two groups were equivalent for sex offenses, while recidivism rates for other crimes were significantly higher among offenders who did not receive the sentencing alternative. Overall, the results provide support for the availability of a sentencing alternative for certain sex offenders